Global trends in surface ocean pCO(2) from in situ data - Fay, A. R.; Mckinley, G. A. (Global Biogeochemical Cycles, 2013)
Ocean carbon uptake substantially reduces the rate of anthropogenic carbon accumulation in the atmosphere and thus slows global climate change. In the interest of understanding how this ocean carbon sink has responded to climate variability and climate change in recent decades, trends in globally observed surface ocean partial pressure of CO2 (pCO(2)(s.ocean)) are evaluated over 16 gyre-scale biomes covering the globe. pCO(2)(s.ocean) trends have been of variable magnitude and sensitive to the chosen start and end years. On longer time frames, several regions of the tropics and subtropics display pCO(2)(s.ocean) trends that are parallel to or shallower than trends in atmospheric pCO(2), consistent with the ocean's long-term response to carbon accumulation in the atmosphere and with the supply of waters with low anthropogenic carbon from the deep ocean. Data are too sparse in the high latitudes to determine this long-term response. In many biomes, pCO(2)(s.ocean) trends steeper than atmospheric trends do occur on shorter timescales, which is consistent with forcing by climatic variability. In the Southern Ocean, the influence of a positive trend in the Southern Annular Mode has waned and the carbon sink has strengthened since the early 2000s. In North Atlantic subtropical and equatorial biomes, warming has become a significant and persistent contributor to the observed increase in pCO(2)(s.ocean) since the mid-2000s. This long-term warming, previously attributed to both multidecadal climate variability and anthropogenic forcing, is beginning to reduce ocean carbon uptake.